Modeling a sonoluminescing bubble as a plasma - Burnett, P; Chambers, D; Heading, D; Machacek, A; Moss, W; Rose, S; Schnittker, M; Lee, R; Young, P; Wark, J (2001)
We present detailed simulations of the optical spectra emitted from an Argon plasma whose conditions correspond to those thought to prevail within sonoluminescing bubbles. The model incorporates detailed atomic physics based on atomic data from the Opacity Project database, and includes bound-bound, bound-free, and free-free transitions. Line broadening is treated by use of the modified semi-empirical method. The spectral model is used as a postprocessor of hydrodynamic simulations. We find good agreement with experimental spectra and accurately reproduce experimental pulse widths. We also predict that whilst the majority of the optical emission corresponds to bound-free transitions, there remains the possibility of observing line emission in both the UV and IR regions of the spectrum. © 2001 Elsevier Science Ltd. All rights reserved.